Kepemimpinan Transformasional Kepala Sekolah dalam Optimalisasi Pembiayaan Pendidikan di Sekolah Dasar Negeri 1 Rancabanteng - Yuliono Yuliono; Iqlima Aviatul Hikmah; Siswadi Siswadi (ARZUSIN, 2026)
Although transformational leadership has been widely discussed in educational management, empirical studies that specifically link its implementation to the management of educational financing in primary schools remain limited. This study aims to examine the role of transformational leadership in optimizing the management of educational financing and to describe its concrete implementation at Sekolah Dasar Negeri 1 Rancabanteng, Wangon Subdistrict. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal and two teachers, observation, and document analysis. The data were analyzed using the Miles and Huberman technique through the stages of data reduction, data display, and conclusion drawing. The results showed that the principal consistently implemented the four dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, thereby producing a participatory and transparent budget management system. These findings indicate that transformational leadership transforms the management of educational financing from an administrative function into a strategic instrument for improving educational quality. The conclusion of this study confirms that the principal’s transformational leadership competence is a key factor in realizing educational financing governance that is transparent, participatory, and quality-oriented. The implications of this study emphasize that transformational leadership deserves to be integrated into principal development policies and educational financial management reform.